Genetic Diversity, Distribution, and Genomic Characterization of Antibiotic Resistance and Virulence of Clinical Pseudomonas aeruginosa Strains in Kenya - Kiyaga, Shahiid; Kyany'a, Cecilia; Muraya, Angela W.; Smith, Hunter J.; Mills, Emma G.; Kibet, Caleb; Mboowa, Gerald; Musila, Lillian (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa is a leading cause of nosocomial infections worldwide. It can produce a range of debilitating infections, have a propensity for developing antimicrobial resistance, and present with a variety of potent virulence factors. This study investigated the sequence types, phenotypic antimicrobial susceptibility profiles, and resistance and virulence genes among clinical isolates from urinary tract and skin and soft tissue infections. Fifty-six P. aeruginosa clinical isolates were obtained from six medical centers across five counties in Kenya between 2015 and 2020. Whole-genome sequencing was performed to conduct genomic characterization, sequence typing, and phylogenetic analysis of the isolates. Results showed the presence of globally distributed high-risk clones (ST244 and ST357), local high-risk clones (ST2025, ST455, and ST233), and a novel multidrug-resistant (MDR) clone carrying virulence genes (ST3674). Furthermore, 31% of the study isolates were found to be MDR with phenotypic resistance to a variety of antibiotics, including piperacillin (79%), ticarcillin-clavulanic acid (57%), meropenem (34%), levofloxacin (70%), and cefepime (32%). Several resistance genes were identified, including carbapenemases VIM-6 (ST1203) and NDM-1 (ST357), fluoroquinolone genes, crpP, and qnrVCi, while 14 and 22 different chromosomal mutations were detected in the gyrA and parC genes, respectively. All isolates contained at least three virulence genes. Among the virulence genes identified, phzB1 was the most abundant (50/56, 89%). 21% (12/56) of the isolates had the exoU+/exoS- genotype, while 73% (41/56) of the isolates had the exoS+/exoU- genotype. This study also discovered twelve novel lineages of P. aeruginosa, of which one (ST3674) demonstrated both extensive antimicrobial resistance and the highest number of virulence genes (236/242, 98%). Although most high-risk clones were detected in Nairobi County, high-risk and clones of interest were found throughout the country, indicating the local spread of global epidemic clones and the emergence of new strains. Thus, this study illustrates the urgent need for coordinated local, regional, and international antimicrobial resistance surveillance efforts.